Strategi Integrated Marketing Communications (IMC) Marrs.Id untuk Menarik Minat Beli Konsumen - Naufal Feraldy Nopal; Aning Sofyan (Bandung Conference Series: Communication Management, 2023)
Abstract. UMKM are part of the national economy that is self-reliant and has great potential to improve people's welfare. UMKM have a significant role in the country's economic growth. In running its business, a marketing strategy is needed to increase someone's buying interest. This study examines the integrated marketing communication strategy carried out by one of the UMKM in Kuningan Regency, namely Marrs.id. The purpose of this study is to find out the Integrated Marketing Communication strategy carried out by Marrs.id in increasing consumer buying interest. This study uses a qualitative descriptive research method in order to describe the situation that will be observed in the field more specifically, transparently, and in depth. Data collection techniques using data triangulation, namely observation, interviews, and documentation. The results of this study indicate that Marrs.id uses an integrated marketing communication strategy in various ways including advertising strategies on print, digital, internet, direct marketing on e-commerce, digital/internet marketing on social media such as Instagram, tiktok, sales promotion with providing discounts and sample products, undergoing social action as a sociopreneur, personal selling strategy by participating in events/exhibitions, and the advantages of being able to promote products as widely as possible and the drawback is that there are strategies that have not been maximized by Marrs.id Abstrak. UMKM merupakan bagian dari perekonomian nasional yang berwawasan kemandirian dan memiliki potensi besar untuk meningkatkan kesejahteraan masyarakat. UMKM memiliki peran yang signifikan terhadap pertumbuhan ekonomi negara. Dalam menjalankan usahanya diperlukan strategi pemasaran agar meningkatnya minat beli seseorang. Penelitian ini meneliti tentang strategi integrated marketing communication yang dilakukan oleh salah satu UMKM yang ada di Kabupaten Kuningan yaitu Marrs.id. Tujuan dari penelitian ini yaitu Untuk mengetahui strategi Integrated Marketing Communication yang dilakukan oleh Marrs.id dalam meningkatkan minat beli konsumen. Penelitian ini menggunakan metode penelitian deskriptif kualitatif agar bisa mendeskripsikan keadaan yang akan diamati di lapangan dengan lebih spesifik, transparan, dan mendalam. Teknik pengumpulan data menggunakan triangulasi data yaitu observasi, wawancara, dan dokumentasi. Hasil pada penelitian ini menunjukan bahwa Marrs.id menggunakan Strategi integrated marketing communication dengan berbagai cara diantaranya terdapat strategi advertising pada media cetak, digital, internet, direct marketing pada e commerce, digital/internet marketing pada social media seperti instagram, tiktok, sales promotion dengan memberikan diskon dan produk sample, menjalani aksi social sebagai sociopreneur, strategi personal selling dengan mengikuti event/pameran, dan adanya kelebihan yaitu bisa mempromosikan produk seluas-luasnya dan kekurangannya yaitu terdapat strategi yang belum maksimal yang diterapkan oleh Marrs.id.